2019 Levels of Digital Preservation - National Digital Stewardship Alliance (NDSA) (Open Science Framework, 2022)
The NDSA launched the Levels of Preservation guidelines in 2013. In 2018, the NDSA created a group to review and update the 2013 levels. Groups consisted of interested community members and the work done was reviewed by an even larger community. The Levels serve to be a tiered set of recommendations on what organizations could do to build or enhance their digital preservation activities.